Rancang Bangun Sistem Informasi Konferensi Internasional ICBB UHW Perbanas Berbasis Website menggunakan Framework Codeigniter - Mukhlis, Iqbal Ramadhani; Afandi, Haekal Ridho (Fakultas Teknologi Informasi Institut Teknologi Adhi Tama Surabaya, 2024)
Conferences are meetings whose purpose is to exchange thoughts and opinions on common issues. Advances in technology make people believe that work is more effective and efficient. One of them is changing the traditional system into a computerized system. Conference organizers more effectively disseminate information, record, broadcast, and conduct other conference activities using Internet-enabled web services. ICBB is an international conference held by UHW Perbanas since 2010. The author designed a website-based information system using the CodeIgniter Framework. The system development methodology adopted is the Waterfall method. Based on the results of external and internal testing, a value of 80.8% was obtained, which concluded that the information system was feasible and could make it easier for participants to find information related to the publication of research papers and community service scripts and to increase the ease of managing ICBB within the Perbanas UHW environmentKeywords: Website, Information System, CodeIgniter, ICBB, UHW Perbanas, Waterfall